2006
DOI: 10.1073/pnas.0603349103
|View full text |Cite
|
Sign up to set email alerts
|

TEL-AML1 transgenic zebrafish model of precursor B cell acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is a clonal disease that evolves through the accrual of genetic rearrangements and͞or mutations within the dominant clone. The TEL-AML1 (ETV6-RUNX1) fusion in precursor-B (pre-B) ALL is the most common genetic rearrangement in childhood cancer; however, the cellular origin and the molecular pathogenesis of TEL-AML1-induced leukemia have not been identified. To study the origin of TEL-AML1-induced ALL, we generated transgenic zebrafish expressing TEL-AML1 either ubiquitously o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 49 publications
1
134
0
1
Order By: Relevance
“…Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia. Both cancers also displayed similar properties with respect to mammals (Sabaawy et al, 2006;Chen et al, 2007).…”
Section: Transgenic Linesmentioning
confidence: 69%
See 1 more Smart Citation
“…Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia. Both cancers also displayed similar properties with respect to mammals (Sabaawy et al, 2006;Chen et al, 2007).…”
Section: Transgenic Linesmentioning
confidence: 69%
“…In a separate study, the same group showed that irradiation or dexamethasone-induced apoptosis of fish leukemic cells is dependent on bcl-2 gene function that also operates in mammalian forms of leukemia (Langenau et al, 2005b). Two independent studies used a similar approach to induce different subtypes of leukemia mediated by overexpression of the aberrant TEL-AML1 fusion protein using the ubiquitous b-actin promoter or overexpression of Notch using the rag2 promoter (Sabaawy et al, 2006;Chen et al, 2007). Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia.…”
Section: Transgenic Linesmentioning
confidence: 99%
“…To capitalize on the powerful developmental and genetic tools available in zebrafish, researchers have created numerous zebrafish tumor models (Langenau et al, 2003Yang et al, 2004;Berghmans et al, 2005;Patton et al, 2005;Haramis et al, 2006;Sabaawy et al, 2006;Le et al, 2007). The ultimate goal of the majority of this work is to identify pathways that modify disease states.…”
mentioning
confidence: 99%
“…Transgenic TEL-AML1 expression did not induce leukemia either in vitro using human HSC, or in vivo using transgenic mice and zebrafish models, but increased the self-renewal of B-cell progenitors and the number of HSC (19)(20)(21)(22)(23). Twin studies and analysis of cord blood samples demonstrates that the childhood leukemia development is initiated in utero (24,25).…”
Section: Tel-aml1 Fusion Genementioning
confidence: 99%